2018
DOI: 10.1111/1440-1630.12483
|View full text |Cite
|
Sign up to set email alerts
|

A pre‐post evaluation of a knowledge translation capacity‐building intervention

Abstract: The KT capacity-building intervention changed one clinician-reported behaviour and perceived impact of barriers across six domains. Clinicians reported perceived improvement in understanding of - and confidence in - KT, and changes in the culture to one of engaging with KT as part of clinical practice. Further research into KT capacity building is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(68 citation statements)
references
References 34 publications
2
66
0
Order By: Relevance
“…Alarmingly, up to 70% of all organizational improvement efforts fail (4). Key barriers include lack of knowledge and skills, lack of time, competing priorities of organizations, and lack of leadership endorsement (5,6,7). Important enablers include health care professionals' (HCPs) positive beliefs about the consequences of participation in training programs, combined with expert guidance and organizational support (8).…”
Section: Contributions To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Alarmingly, up to 70% of all organizational improvement efforts fail (4). Key barriers include lack of knowledge and skills, lack of time, competing priorities of organizations, and lack of leadership endorsement (5,6,7). Important enablers include health care professionals' (HCPs) positive beliefs about the consequences of participation in training programs, combined with expert guidance and organizational support (8).…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…Involving those who use research knowledge in efforts to implement the knowledge has multiple bene ts, including enhancing the effectiveness of implementation efforts (10). Eames and colleagues, for example, found changes in clinician-reported behaviour following participation in their KT capacity-building intervention for occupational therapists, as well as changes in the culture to one in which clinicians engaged in KT as part of their clinical practice (6). A longitudinal evaluation of a program for implementers, called Practicing KT, showed increased use of, knowledge of, and self-e cacy in KT among those who completed the program (5).…”
Section: Contributions To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Aligned with an emphasis on building KT competencies, there has been a growth in curriculumbased initiatives to foster KT practice among knowledge users [9]. The target audiences of these training initiatives vary; some have focused exclusively on a group with a shared background, such as researchers [10] or discipline-specific knowledge users (e.g., occupational therapists [11] or primary care providers [6]). Other initiatives have capitalized on potential benefits of interprofessional learning and collaboration with mixed backgrounds recruited as individuals or teams across healthcare organizations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable research regarding the effects of training on skill acquisition (Arthur et al, 2003; Blume et al, 2010), less is known regarding how change-related training contributes to the dissemination of knowledge and skills from trainees to their peers (Bell, Tannenbaum, Ford, Noe, & Kraiger, 2017). Recent studies have identified the role of training as a change vehicle for change-related learning (Sartori, Costantini, Ceschi, & Tommasi, 2018), and examined the effect of a knowledge translation intervention on practitioners’ engagement in new clinical practices (Eames et al, 2018) As yet little is known about how training might contribute to the diffusion of organizational change. Nonetheless, training can play a special role in technological change if it contributes to the dissemination of change-related knowledge and skills (Jacobs & Russ-Eft, 2001).…”
mentioning
confidence: 99%